Perceived neighbourhood safety moderates the relationship between active school travel and health-related quality of life. (July 2021) - Martin, Gina; Graat, Megan; Medeiros, Alina; Clark, Andrew F.; Button, Brenton L.G.; Ferguson, Kendra Nelson; Gilliland, Jason A.
Abstract: There is a dearth of studies examining associations between active school travel and children's health-related quality of life. Additionally, studies have not examined how perceived neighbourhood characteristics may moderate these associations. This study aims to examine the relationship between regular active school travel, children's physical and psychosocial health-related quality of life, and the potential moderating effects of their perceived neighbourhood safety (interpersonal and traffic). This cross-sectional study used data from Ontario schoolchildren (aged 8–14) as part of the Spatial Temporal Environment and Activity Monitoring (STEAM) Project. Results showed no significant direct relationship between regular active school travel and children's physical or psychosocial functioning; but the relationships were moderated by perceived neighbourhood safety. Regular active school travelers with high levels of perceived neighbourhood interpersonal safety, had higher physical and psychosocial functioning than regular active school travelers with low levels of perceived neighbourhood interpersonal safety. Additionally, at higher levels of perceived neighbourhood traffic safety, regular active school travelers had higher psychosocial functioning than regular active school travelers with lower perceived neighbourhood traffic safety. Interventions promoting active school travel should consider the environments through which children will be traveling. Highlights: There were no significant relationships between regular active school travel and health-related quality of life. Perceived neighbourhood safety moderated relationships between active school travel and health-related quality of life. Associations among active school travel and health-related quality of life may be impacted by neighbourhood characteristics.